Adolescents with idiopathic scoliosis show decreased intermuscular coherence in lumbar paraspinal muscles: A new pathophysiological perspective. (June 2022) - Simoneau, Martin; Pialasse, Jean-Philippe; Mercier, Pierre; Blouin, Jean-Sébastien
Highlights: Adolescent idiopathic scoliosis (AIS) exhibited smaller alpha and beta band intermuscular coherence between lumbar muscles during steady isometric contractions. Reduced coupling in alpha and beta bands suggest alterations in the spinal and/or sensorimotor control of the axial musculature. In participants with AIS, the smaller intermuscular coupling in the alpha band was associated with larger phase variance. Abstract: Objective: Although adolescent idiopathic scoliosis is thought to be an orthopedic disorder, sensorimotor deficits resulting in asymmetric neural drive to the axial musculature have been proposed as contributing factors. Asymmetry in the vestibular control of spinal motoneurons can cause spine deformation reminiscent of idiopathic scoliosis in animal models. Methods: To examine the neural control of axial muscles, we compared common oscillatory drive to bilateral lumbar muscles between 19 participants with adolescent idiopathic scoliosis and 19 healthy adolescents. We measured right and left paraspinal muscle activity during steady isometric back extensions at 15% or 30% of their maximum voluntary contraction. Results: The variance in exerted force and symmetry in bilateral muscle activation were similar between groups. We estimated the strength of common oscillations between muscle motoneuron pools using intermuscular coherence. Compared to controls, participants with adolescent idiopathic scoliosis exhibited smaller intermuscular coherence between paraspinal muscles in the alpha and beta bands. To identify the cause of the observed decreased in intermuscular coherence, we quantified variability of electromyography power ratio and relative activation timing between the paraspinal muscle. Intermuscular phase between muscle oscillations across the alpha band demonstrated larger variability in adolescent with idiopathic scoliosis. The variability of the ratio of lumbar muscles power was similar between groups in the alpha and beta bands. Conclusion: Our results suggest that altered bilateral control of axial muscles characterized by increased variability in the timing of alpha oscillations may be linked to spine deformation in adolescents. Significance: Our findings provide a new perspective on neural factors associated with a common spine deformation, adolescent idiopathic scoliosis.